Knowledge, Attitude and Practice of Community Members Regarding Influenza A H1N1 in Rajkot District, Gujarat, India - Dhara V Thakrar; Jasmin R Oza; Umed V Patel; Dhara N Jahangirporia; Zalak R Matariya; Harshida K Namera (Medsci Publications, 2017)
Back ground: In 2009, a novel strain of influenza A H1N1 emerged from the USA and Mexico. The first confirmed case with the virus in India was documented in May 2009. After that, a large numbers of positive cases were reported throughout India. The objective of this study was to assess knowledge, attitude and practice (KAP) of community members regarding influenza A H1N1. Methods: Out of 14 talukas of Rajkot district, a study was conducted in 7 talukas where positive cases of H1N1 Influenza A were reported by purposive sampling method during March 2015. Total 18 areas were surveyed and total 8 persons each from different family were interviewed, thus total of 144 such persons were interviewed. Results: Most of the respondents were male. Almost half of participants were in age group 21-40 yrs. Majority of them were literate and educated up to secondary level. 93.75% of community members heard about influenza A H1N1. TV (57.78%) was the main source of knowledge.. 65.97% of community members had correct knowledge on any one key symptom of Influenza A (e.g. Fever/Cough/Sore throat). Majority (81.25%) of the persons consult Family/Private doctor for treatment of ARI. Conclusion: Health care service provides and media should take lead in spreading awareness especially during transmission season so that can avoid panic in the community.